2013
DOI: 10.1016/j.febslet.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

X‐box binding protein 1 enhances adipogenic differentiation of 3T3‐L1 cells through the downregulation of Wnt10b expression

Abstract: a b s t r a c tDifferentiation of preadipocytes into adipocytes is controlled by various transcription factors. Recently, the pro-adipogenic function of XBP1, a transcription factor upregulated by endoplasmic reticulum stress, has been reported. In this study, we demonstrated that XBP1 suppresses the expression of Wnt10b, an anti-adipogenic Wnt, during the differentiation of 3T3-L1 preadipocytes. The expression pattern of XBP1 was reciprocal to that of Wnt10b during the early stage of adipogenesis. The intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…L). Although the importance of XBP1s in in vitro adipogenesis has been suggested previously , our findings from XBP1s over‐expression experiments in wild‐type and XBP1‐KD cells and the quantitative measurement of intracellular triacylglycerol contents more reliably suggest that XBP1s is an essential pro‐adipogenic transcription factor, especially in the very early time period of differentiation.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…L). Although the importance of XBP1s in in vitro adipogenesis has been suggested previously , our findings from XBP1s over‐expression experiments in wild‐type and XBP1‐KD cells and the quantitative measurement of intracellular triacylglycerol contents more reliably suggest that XBP1s is an essential pro‐adipogenic transcription factor, especially in the very early time period of differentiation.…”
Section: Resultssupporting
confidence: 52%
“…Given that C/EBPα and Wnt10b, two important regulators for adipogenesis, are target genes of XBP1s , it is plausible that XBP1s may direct adipogenesis by regulation of pro‐ and anti‐adipogenic signalling pathways. Moreover, to our knowledge, in vitro adipogenesis is always suppressed by depletion of XBP1s . Taken together, these findings imply that XBP1s may also play roles in adipose tissue formation in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro, we and others have shown that XBP1s is required (1012), but not sufficient (13) for adipocyte differentiation (i.e., adipogenesis). In vivo, Xbp1 +/− mice exhibit increased IRE1α activation in adipose tissue upon obesity, which subsequently attenuates insulin signaling by modulating the Jun NH 2 -terminal kinase–insulin receptor substrate-1 signaling axis (4).…”
Section: Introductionmentioning
confidence: 85%
“…It has been implicated in the ER expansion in differentiating plasma cells (43,44) and the pancreas and salivary glands (45), gluconeogenesis and lipogenesis in hepatocytes (57,46), adipogenesis (1012), inflammation in macrophages (47) and Paneth cells (48), and control of autophagy in the nervous system (49). Our data further highlight an important role of XBP1s in adiponectin complex formation in adipocytes.…”
Section: Discussionmentioning
confidence: 99%